Matching design for multi-chip module packaging by considering thermal control. (15th October 2008) - Yang, Ping; Qin, Xiangnan; Zhang, Wenbo
The aim of this article is to provide a systematic method to perform optimisation design or evaluation for multi-chip module (MCM) in electronic packaging by considering thermal control. Based on investigation of the parameters characteristics (about structural and thermal physical parameters characteristics) which are originated by design and manufacture, the key performance indexes of MCM that include the lowest internal temperature objective, thermal transfer accuracy, chip placement are analysed. The mapping relations between parameters characteristics of MCM are established on the basis of systematic design point. A GA-RSM model was presented to implement the optimisation. Furthermore, some design processes for improving performance are induced. Finally, an example is discussed to apply the method.